Evaluating the Covid-19 Pandemic's Impact on Indonesia's Economic Growth, Unemployment, and Poverty - Siregar, Diphda Adhara Raseuki; Sari, Dyah Wulan; Islamiyah, Haura Azzahra Tarbiyah (EcceS: Economics, Social, and Development Studies, 2024)
This study discusses the impact of the COVID-19 pandemic in the form of deaths because of COVID-19 and the number of positive cases of COVID-19 on economic growth, unemployment and poverty in 34 provinces in Indonesia. The novelty of the study innovatively analyzes COVID-19's impact on Indonesia's economic growth, unemployment, and poverty using a Three-Stage Least Squares (3SLS) regression, offering robust insights and valuable guidance for comprehensive recovery strategies. The future impact of this study is to provide crucial insights that will guide more effective policy decisions and set a new standard for economic impact research. This research method uses panel regression 3SLS (Three-Stage Least Square), in which this method is used to estimate a system of simultaneous equations. The endogenous variables used in this study are economic growth, unemployment, and poverty while the exogenous variables used in this study consist of labour, wages, COVID-19 death rate, and positive cases of COVID-19. The results obtained in this study show that the COVID-19 pandemic, which consists of the COVID-19 death rate and the positive cases of COVID-19, had a significant effect on Indonesia's economic growth. In addition, the death rate of COVID-19 and positive cases of COVID-19 also have a significant effect on unemployment in Indonesia. Finally, the death rate for COVID-19 and positive cases for COVID-19 also have a significant effect on poverty in Indonesia. The research limitation of this study is that this study only uses the first two years of the COVID-19 pandemic in Indonesia. The implication of this research, the government must prioritize efforts to control the spread of COVID-19 to mitigate its adverse effects on economic growth, unemployment, and poverty.